Aid, Environment and Climate Change. Issue 2 (1st February 2017) - Arndt, Channing; Tarp, Finn
Abstract: Aid and aid institutions constitute an important element of the global response to interlinked global developmental and environmental challenges. As such, these institutions are now being drawn into new arenas beyond the traditional focus on improving the livelihoods of poor people in low‐income countries. Development aid, by itself, cannot "save the planet." Nevertheless, development aid and development institutions do have the potential to become important catalytic actors in achieving developmental and global environmental objectives. This requires bold reforms and political action. Without appropriate restructuring of the international institutional architecture to confront the new development context combined with the necessary complementary policy frameworks, future aid, including aid for environmental objectives, risks substantially under‐performing.